CORRELATION OF EDUCATION LEVEL TO MOTHER’S KNOWLEDGE FOLLOWING THERAPEUTIC FEEDING CENTER (TFC) PROGRAM IN SUKOHARJO CENTRAL JAVA - Rakhma, Luluk Ria; F., Erlinda; F., Apriliana W. (Tadulako University, 2017)
Background & Objective: Malnutrition is still common in many developing countries including Indonesia. Various efforts made by the government to overcome malnutrition. One of them is through nutrition education as in the Therapeutic Feeding Center (TFC) program. Activities that increase knowledge of nutrition will depend highly on the mother’s education level. This study aims to analyze the correlation of education level to mother’s knowledge of children under five following the TFC program in Sukoharjo regency, Central Java. Method : This study used an observational design with Cross Sectional approach which took place in September 2016-February 2017 at Gatak, Weru and Sukoharjo Public Health Center. 35 samples were chosen by Simple Random Sampling technique. The maternal education and nutritional knowledge variables were obtained using questionaires that has been tested for reliability. Statistical analysis using Chi Square. Results: Respondent were mostly mothers with children aged 37-60 months (77.1%), aged <35 years (60%), low family income (62%) and small family (77.1 %). The majority mothers with low education are 54.3% and have good nutritional knowledge of 45.7%. The minimum score of mother's nutritional knowledge is 50 and the maximum is 90 with an average of 68.5 points. The correlation test got a p value of 0.03 with Odd Ratio of 6.2 (1.4-26.9) means that mother with a low education level has a probability 6.2 times higher lack of nutritional knowledge. Conclusion: There is a correlation between education level with knowledge of mother following TFC program in Sukoharjo Regency Central Java